A novel Multiple Attribute Decision-making approach for assessing the effectiveness of advertising to a target audience on drinking water consumers' behavior considering age and education level. (March 2023) - Noori, Amir; Bonakdari, Hossein; Salimi, Amir Hossein; Pourkarimi, Latif; Masoompour Samakosh, Jafar
Abstract: One effective way to cope with water scarcity is to enhance water use efficiency by reforming water customer habits. Owing to the semi-arid climate of Iran, the drinking water consumption rate of urban households is greater than the routine average daily per capita consumption of water. With limited water supply and poor consumption habits, the country needs to reform its water management practices. On the other hand, the influence of advertising types, especially mass media, to improve water consumers' behavior in society is undeniable. Herein, the current study examines the effectiveness of using four advertisement strategies (animation, celebrities, social networks, and conceptual advertising) to modify the public's drinking water consumption. The statistical population in this study included urban households in four critical cities subjected to intense water stress, including Tehran, Isfahan, Shiraz, and Kermanshah. In order to evaluate the impact of the advertisement strategy on residents, the most important questions were extracted and used to prepare a questionnaire with 24 indicators. Afterward, a novel Multiple Attribute Decision-making (MADM) based methods was designed to consider the importance weights of age and education level on respondents to estimate the questionnaire accuracy. The dominant strategy by applying age and education level influence for each city was using animation in Tehran, followed by a conceptual advertisement in Isfahan and Shiraz, and the social network in Kermanshah. Further, as a statistical examination using SPSS software, the Spearman test was employed to analyze the questionnaire and its results without the impact of age and education level. The results obtained in the developed technique compared with the analyzed results of statistical test showed that the application of age and education level will significantly impact advertising comprehension and validation of results.